2001
DOI: 10.1021/ma001388l
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Structural Relaxation of Partially Disentangled Poly(vinyl chloride) Prepared by Freeze-Extracting Dilute Solutions

Abstract: The partially disentangled poly(vinyl chloride) (PVC) samples were prepared by freezeextracting from dilute PVC/THF solutions. The conformation of these samples was investigated by infrared and Raman spectroscopy. The structural relaxation behaviors were studied by differential scanning calorimeter (DSC). The results showed that the PVC samples prepared from dilute solutions with concentrations lower than 0.25% were in the expanded state with fewer entanglements. The conformation and structural relaxation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…12 We also found that the molar volume of solvents plays an important role in the entanglement state of polymer in solution. [13][14][15] Therefore, it is necessary for us to explore the effect of solvent on the conformation of PVC.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…12 We also found that the molar volume of solvents plays an important role in the entanglement state of polymer in solution. [13][14][15] Therefore, it is necessary for us to explore the effect of solvent on the conformation of PVC.…”
Section: Introductionmentioning
confidence: 63%
“…In our previous paper, we reported that the PVC sample prepared from very dilute solution in THF was in the expanded state with fewer entanglements which would result a higher crystallinity than samples prepared from more concentrated solution. 12 In the IR spectra shown in Figure 1, the change in relative intensity of the 1427 and 1435 cm -1 bands and the increased intensity of a crystalline bands at 638 cm -1 in curve A indicate that an ordering takes place in PVC due to effect of partly disentanglement of polymer chain in concentrated solution in DOP. PVC freeze-extracted from 5 wt % in DOP has relatively high content of crystalline units, as shown in Figure 1A, while Figure 1B,C illustrates the amorphous morphology of the polymer samples recovered from PVC/THF and PVC/DMP.…”
Section: Resultsmentioning
confidence: 95%
“…The results showed that the PVC samples prepared from dilute solutions (<0.25 wt%) were in the expanded state with fewer entanglements, which makes a limited crystallization after annealing of polymer just above T g easier. The structural relaxation rate, observed as a magnitude of the endothermic peak at glass transition, increased with decreasing chain entanglements (i.e., with a lower concentration of initial solution) . Surprisingly, for the same PVC it was discovered that when the solvent was dioctyl phthalate, having a large molecular volume, then the polymer prepared from 5 wt% solution shows similar crystallization behavior as PVC from very dilute solution, suggesting that the extent of chain interpenetration in this concentrated solution was similar to that in the very dilute solutions in THF …”
Section: Properties Of Polymers With Limited Density Of Entanglementsmentioning
confidence: 96%
“…The structural relaxation rate, observed as a magnitude of the endothermic peak at glass transition, increased with decreasing chain entanglements (i.e., with a lower concentration of initial solution). [110] Surprisingly, for the same PVC it was discovered that when the solvent was dioctyl phthalate, having a large molecular volume, then the polymer prepared from 5 wt% solution shows similar crystallization behavior as PVC from very dilute solution, suggesting that the extent of chain interpenetration in this concentrated solution was similar to that in the very dilute solutions in THF. [75] The properties of disentangled materials were studied only for homopolymers, with the exception of Yang's et al work, [165] where the extrusion with injection was used for blending HDPE with 0-10 wt% of commercial, entangled UHMWPE or with synthesized, partially disentangled UHMWPE.…”
Section: Other Observationsmentioning
confidence: 98%
“…In this respect a possible role of the entanglement was invoked. It is also worth noting that it has been recently evidenced the influence of the chain entanglements on the structural relaxation features of polycarbonate [36], polystyrene and poly(ether sulfone) [37] and poly(vinyl chloride) [38] with the use of special drying methods [39][40][41] which provide highly disentangled polymeric systems. In particular after annealing the samples in the glass, the enthalpy recovery measured by DSC thermograms showed a quite different behavior for the disentangled systems with respect to the entangled ones.…”
Section: Theoretical Frameworkmentioning
confidence: 99%